Improved co-optimal and evaluable index of carbon sequestration and enhanced oil recovery. (February 2021) - Zhang, Chao; Wu, Shouya; Li, Zhaomin; Zhao, Dongya; Lv, Guangzhong
To satisfy the requirements of the new technology of carbon capture, utilization, and storage (CCUS), it is recommended that carbon dioxide-enhanced oil recovery (CO2 -EOR) projects change their design objective index by taking carbon sequestration into account, an approach that significantly differs from the traditional design. This study builds a new optimal index function for the new requirement based on the existing indices of the traditional index and the Kovscek index, which are inapplicable for co-optimization. The proposed approach improves the existing methods in terms of the weight function and representation parameters, making the method more suitable for the optimization and evaluation of the carbon sequestration and enhanced oil recovery process. This objective index can be used to obtain the optimization time point. To validate the proposed approach, a CO2 -EOR simulation process has been evaluated using the proposed index, and the optimization time point obtained (the 6054th day, f = 1.001). The optimized process would have a better development effect on CO2 -EOR by comparison of simulation results. Then, this optimal index was applied on a CO2 -EOR project in Wasson oil field. The results suggest that the injection measures should be introduced at the 13th and 17th years, and this improved objective index can be effectively applied to the carbon sequestration and enhanced oil recovery process.